Impact of Ho and Ce Ions Substitution on Structural, Electrical, and Dielectric Properties of Ni-Zn Ferrites - Manzoor, Alina; Javed, Aqib; Muhammad Afzal, Amir; Arshad, M. Imran; Shahzad, Aamir (Journal of Materials and Physical Sciences, 2020)
In the present study, influence of holmium (Ho) and cerium (Ce) ions on the electromagnetic properties of Ni0.67Zn0.33Fe1.9Ho0.1-xCexO4 ferrites (x = 0, 0.025, 0.05, 0.075, 0.1) synthesized by the self-ignited sol-gel method was studied. The XRD experiment was performed to determine the substitutional effects on structural parameters. FTIR spectroscopy and I-V measurements were carried out to analyze the spectral and electrical behavior of substituted samples. X-ray diffraction patterns revealed the FCC structure of the prepared samples The value of average crystallite size was noticed between 25.89-39.51 nm, while lattice constant was found in the range 8.37-8.41 Å. Both the low and the high frequency absorption bands were confirmed by FTIR technique. Tetrahedral band was noted in the range 463-495 cm-1 while octahedral band was observed in range 558-560 cm-1. The dc resistivity was observed to decrease with increase in temperature which indicates the semi-conductor like behavior of the prepared samples. Dielectric study showed that both the dielectric constant and the tangent loss factor were decreased with rise in the applied field frequency.